Epigenetic silencing of CYP24 in tumor-derived endothelial cells contributes to selective growth inhibition by calcitriol - Chung, I.; Karpf, A.R.; Muindi, J.R.; Conroy, J.M.; Nowak, N.J.; Johnson, C.S.; Trump, D.L. (2007)
Calcitriol (1,25-dihydroxycholecalciferol), the most active form of vitamin D, has selective anti-proliferative effects on tumor-derived endothelial cells (TDEC) compared with Matrigel-derived endothelial cells (MDEC). Although both cell types have an intact vitamin D receptor-signaling axis, this study demonstrates that upon treatment with calcitriol, 24-hydroxylase (CYP24) mRNA, protein and enzymatic activity were markedly induced in MDEC in a time-dependent manner but not in TDEC. Furthermore, treatment of MDEC with a CYP24 small interfering RNA restored sensitivity to calcitriol. To investigate the lack of CYP24 induction in TDEC, we examined methylation patterns in the promoter regions of the CYP24 gene in these two cell types. We identified two putative CpG island regions located at the 5' end. Using methylation-specific PCR and bisulfite sequencing, we determined that these CpG islands were hypermethylated in TDEC but not in MDEC. These data may explain the recruitment of vitamin D receptor to the promoter region in MDEC but not TDEC, as revealed by chromatin immunoprecipitation analyses. Treatment of TDEC with the DNA methyltransferase inhibitor 5-aza-2'-deoxycytidine restored calcitriol-mediated induction of CYP24, which led to loss of sensitivity to calcitriol growth inhibitory effects. CYP24 promoter hypermethylation was also observed in endothelial cells isolated from other tumors but not in endothelial cells isolated from normal mouse tissues. These observations indicate that the methylation status of the CYP24 promoter differs in endothelial cells isolated from different microenvironments (tumor versus normal) and that methylation silencing of CYP24 contributes to selective calcitriol-mediated growth inhibition in endothelial cells.